Everyday Students’ Behaviour of Ukrainian Universities of the First Half of 19th Century - Петровський, Володимир; Семененко, Валерій (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The analysis of features of daily behavior of students of Russian Ukrainian universities during the first half of XIX century is given in this article. The prerequisites that caused prevalence of prohibited events in educational system of Russian Empire are ascertained. Investigation of sources and printed works shows that the students didn’t perceive agents’ espionage actions, inspection’s rudeness. It’s proved that majority of students’ deeds was generally based on an increased sense of justice.